2003
DOI: 10.1023/a:1023410302898
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A threshold model postulates that prescriptively applying the appropriate cardiorespiratory and strength stimulus at a designated threshold of intensity for a brief time results in the targeted adaptations. A randomized control group design was used with 17 unfit males and females (mean age = 37.1 +/- 6.5 year) assigned to an exercise group (n = 9) who performed a progressive cardiovascular graded exercise protocol and resistance training twice a week for 12 weeks or a nonexercising control group (n = 8). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this study, the RT was done before than HIIT which it is the order that had better results to increase 1RM [5,6]. A study of Winett et al [33] found that even lowvolume CT was able to improve strength in various exercises in untrained subjects. Another article methodologically similar to our study, which prescribed a higher daily volume for both of RT and AT, they found improvements in strength in the half squat [34].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the RT was done before than HIIT which it is the order that had better results to increase 1RM [5,6]. A study of Winett et al [33] found that even lowvolume CT was able to improve strength in various exercises in untrained subjects. Another article methodologically similar to our study, which prescribed a higher daily volume for both of RT and AT, they found improvements in strength in the half squat [34].…”
Section: Discussionmentioning
confidence: 96%
“…When measuring CRF through VO 2max , there is more evidence pointing in the same way. A work of Winett et al [33] who performed a low-volume CT protocol achieved signi cant improvements in VO 2max in untrained subjects during 12 weeks of training. When addressing CT with a higher volume there is a wide literature that indicated to signi cant improvements of VO 2max [38,[45][46][47].…”
Section: Discussionmentioning
confidence: 96%
“…who studied low volume CT for 12 weeks in untrained individuals did not obtain significant results in terms of body composition (i.e., TBM and %FM). 36 However, Ghahramanloo et al. reported significant improvements in %FM and FFM for the group that performed CT in college students.…”
Section: Discussionmentioning
confidence: 97%
“… 52 In relation to articles that studied the low volume of CT in muscle strength, measured through other resources, we can verify that after 12 weeks of CT reported a significant increase in the 6 RM test in various resistance exercises, in untrained adult men and women. 36 Another study investigated the effects of CT by performing only half of the target repetitions of each series in the RT, “ effort character ” of 50%, which culminated in a lower training volume at the end of the 8 weeks, however, the results revealed a significant increase in 1RM in several resistance exercises in untrained hospital workers. 53 Despite the lack of evidence, traditional CT in active young adults generates significant increases in muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…have previously demonstrated that most of the effect of aerobic training is attained when the high-intensity threshold is passed for only a few minutes [76]. This implies that the time for effective exercise can be substantially reduced.…”
Section: How To Effectively Improve Cardiorespiratory Fitness (Crf)?mentioning
confidence: 99%